2016
DOI: 10.1186/s13046-016-0425-9
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock protein 70-2 (HSP70-2) overexpression in breast cancer

Abstract: BackgroundBreast cancer is one of the leading cause of cancer-related deaths in women worldwide and increasing rapidly in developing countries. In the present study, we investigated the potential role and association of HSP70-2 with breast cancer.MethodsHSP70-2 expression was examined in 154 tumor and 103 adjacent non-cancerous tissue (ANCT) specimens and breast cancer cell lines (MCF7, BT-474, SK-BR-3 and MDA-MB-231) by RT-PCR, quantitative-PCR, immunohistochemistry, Western blotting, flow cytometry and indir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 27 publications
(39 reference statements)
0
49
3
Order By: Relevance
“…Recently, it has been found that HSP72 (HSP70) plays an essential role in organizing kinetochore-associated microtubules for amplified centrosomes, a cancer specific phenotype which, if not stabilized, triggers mitotic catastrophe and apoptosis [53]. In addition, increased levels of HSP70B (HSP70) contribute to breast cancer metastasis through upregulation of mesenchymal markers such as N-cadherin, MMP2, SNAIL, and vimentin [54]. Furthermore, HSC70 overexpression enhances the glioma cell proliferation, migration, and invasion through phosphorylation and activation of FAK, Src, and Pyk2.…”
Section: Role Of Hsp70 In Cancer Developmentmentioning
confidence: 99%
“…Recently, it has been found that HSP72 (HSP70) plays an essential role in organizing kinetochore-associated microtubules for amplified centrosomes, a cancer specific phenotype which, if not stabilized, triggers mitotic catastrophe and apoptosis [53]. In addition, increased levels of HSP70B (HSP70) contribute to breast cancer metastasis through upregulation of mesenchymal markers such as N-cadherin, MMP2, SNAIL, and vimentin [54]. Furthermore, HSC70 overexpression enhances the glioma cell proliferation, migration, and invasion through phosphorylation and activation of FAK, Src, and Pyk2.…”
Section: Role Of Hsp70 In Cancer Developmentmentioning
confidence: 99%
“…Hsp70 binds tumour-suppressor proteins, determining unlimited cellular growth and increased resistance to chemotherapy in breast cancer [ 88 , 92 ]. On the contrary, downregulation of Hsp70 levels in some types of cancers induces differentiation and cell death [ 93 ]. Hsp70 can trigger the activation of the immune response by stimulating both innate and adaptive immunities.…”
Section: Hsp70mentioning
confidence: 99%
“…Also, HSP70 and HSP90 participate in many key processes in oncogenesis such as self-sufficiency in growth signals, stabilization of mutant proteins, angiogenesis, and metastasis. They act like antiapoptotic chaperones (23,24,25). In our study, HSP70 and HSP90 gene expressions were studied in MM cells and PCL cell lines.…”
Section: Discussionmentioning
confidence: 98%